2012
DOI: 10.3402/dfa.v3i0.12169
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of re-amputation following partial first ray amputation associated with diabetes mellitus and peripheral sensory neuropathy: a systematic review.

Abstract: Diabetes mellitus with peripheral sensory neuropathy frequently results in forefoot ulceration. Ulceration at the first ray level tends to be recalcitrant to local wound care modalities and off-loading techniques. If healing does occur, ulcer recurrence is common. When infection develops, partial first ray amputation in an effort to preserve maximum foot length is often performed. However, the survivorship of partial first ray amputations in this patient population and associated re-amputation rate remain unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 26 publications
3
33
1
Order By: Relevance
“…However, the results have failed to meeting expectations, partially due to relapse. 35 In the last decades, cellular therapy has emerged as a potential strategy for treatment of CLI in patients. Since the discovery of BMCs in peripheral circulation, 1 the regenerative property of BMCs has been studied extensively.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results have failed to meeting expectations, partially due to relapse. 35 In the last decades, cellular therapy has emerged as a potential strategy for treatment of CLI in patients. Since the discovery of BMCs in peripheral circulation, 1 the regenerative property of BMCs has been studied extensively.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent review reported that 1 out of every 5 patients undergoing any version of a partial first ray amputation will eventually require more proximal reamputation. 31 The authors conclude that a more proximal amputation, such as a balanced transmetatarsal amputation, as the index amputation may be more beneficial to the patient. However, this remains a matter for conjecture due to the limited data available and, therefore, additional prospective investigations are warranted.…”
Section: Osteomyelitis Of the Metatarsophalangeal Joint Of The Halluxmentioning
confidence: 96%
“…Borkosky et al (8) reported a 19.8% incidence of re-amputation in patients with diabetes and peripheral sensory neuropathy undergoing partial first ray resection. Wong et al (9) reported a 70% success rate of ray amputation in a cohort of 150 patients with diabetic foot problems.…”
Section: Distal or Minor Amputations For The Diabetic Footmentioning
confidence: 99%